Wood Anatomy of the Tribe Briedelieae (Euphorbiaceae S.L.) Reflecting the Systematic, Ecological and Evolutionary Aspects - Jangid, Prem Prakash; Gupta, Sangeeta (Indian Forester, 2015)
The present paper provides comprehensive wood anatomical survey of seven Indian species belonging to two genera Briedelia and Cleistanthus of the tribe Briedelieae (Euphorbiaceae s.l.). Wood microstructure of Cleistanthus found heterogeneous in certain extent within tribe. Systematic relationships between Briedelia and Cleistanthus were evaluated. The systematic wood anatomical study did not favour the recent morphological and molecular phylogenetic circumscription of classification of the tribe. Cleistanthus showed adaptation to xeric environment and Briedelia showed adaptation to mesic environment. Briedelia contain most of advance wood anatomical features while Cleistanthus had a combination of both advance and primitive wood anatomical features.